2016
DOI: 10.1038/emi.2016.38
|View full text |Cite
|
Sign up to set email alerts
|

Predominance and high antibiotic resistance of the emerging Clostridium difficile genotypes NAP CR1 and NAP9 in a Costa Rican hospital over a 2-year period without outbreaks

Abstract: Clostridium difficile is the major causative agent of nosocomial antibiotic-associated diarrhea. In a 2009 outbreak of C. difficile-associated diarrhea that was recorded in a major Costa Rican hospital, the hypervirulent NAP1 strain (45%) predominated together with a local genotype variant (NAPCR1, 31%). Both strains were fluoroquinolone-resistant and the NAPCR1 genotype, in addition, was resistant to clindamycin and rifampicin. We now report on the genotypes and antibiotic susceptibilities of 68 C. difficile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 45 publications
(63 reference statements)
0
11
0
Order By: Relevance
“…C. difficile NAP CR1 /RT012/ST-54 isolates caused an epidemic in Costa Rica and are now widely distributed in hospitals from this country (López-Ureña et al, 2016 ). Genome sequence analysis of several of these isolates in an earlier study revealed the presence of prophages that were novel, particularly in genome size and composition compared to other C. difficile phage genomes (Ramírez-Vargas et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…C. difficile NAP CR1 /RT012/ST-54 isolates caused an epidemic in Costa Rica and are now widely distributed in hospitals from this country (López-Ureña et al, 2016 ). Genome sequence analysis of several of these isolates in an earlier study revealed the presence of prophages that were novel, particularly in genome size and composition compared to other C. difficile phage genomes (Ramírez-Vargas et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the epidemiology of CDI changes over time in groups at risk of infection and in dominant strains (Goudarzi et al, 2014 ), such that now community-acquired CDI is more prevalent and the “hypervirulent” epidemic NAP1/RT027 strains are no longer predominant. Instead, the NAP7/RT078 or NAP9/RT017 strains are emerging among humans and animals from Asia, Australia, Costa Rica (López-Ureña et al, 2016 ) and other regions of the world (Janoir, 2016 ). Although reasons for this change are unclear, phage and other mobile genetic elements (MGE) are thought to contribute to the evolution of C. difficile , as it has been demonstrated for other human pathogens (Davies et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NAP CR1 /ST54 strains show high virulence in animal models despite their close phylogenetic relationship to nonepidemic ST54 isolates such as the C. difficile reference strain 630 (CD630) ( Quesada-Gómez et al. 2015 ; López-Ureña et al. 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…NAP CR1 isolates induced a severe clinical presentation, were associated with mortality and recurrence rates comparable to those of NAP1/RT027 strains, and produced a strong inflammatory reaction in animal models (12). These strains continue to circulate in several hospitals of this Central American country (13), and their closest known relative is the multidrug-resistant (MDR) strain CD630, which is also classified as RT012/ST-54 and has been claimed to carry bona fide determinants for tetracycline, erythromycin, daunorubicin, bacitracin, nogalamycin, beta-lactam, tellurite, streptogramin, and lantibiotic resistance (14).…”
mentioning
confidence: 99%